การศึกษาแนวทางการลดปริมาณฝุ่นละอองที่ส่งผลกระทบต่อคนงานในหน่วยงานก่อสร้าง - ยรรยง อาภาอนันต์ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
Dust is an important problem of air pollution. The construction area is the major source of dust occurrence. Nowadays, the method of the dust protection in the construction site is to protect the dust affect to outside construction area. However, the method to reduce dust from construction activities affected to workers in construction site was not considered. The objectives of this research are to study construction activities which are the sources of dust and study the guidelines to reduce quantity of dust by improving construction methods. The results of research present that construction activities which are the source of dust such as earth works, concrete works, timber works, system works, transportation activities, materials storage, architectural works and decoration works. In addition, the results of research show that the activities in architectural works and decoration works which are the sources of dust such as cutting, polishing, chiseling, drilling, waste dropping and spreading. From the 3 case studies such as tiling work, ceiling board cutting work and floor polishing work, the results show that protection of dust occurrence and using appropriate construction tools can reduce the dust affect to workers in construction sites around 3-6 times. From the results of cost comparison in case studies, cost of tiling work and ceiling board cutting work with protection of dust occurrence is lower than without protection of dust occurrence. However, cost of floor polishing work with protection of dust occurrence is higher than without protection of dust occurrence.